1992
DOI: 10.1111/j.1440-1819.1992.tb02855.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Prolonged Bed Rest and Cognitive Impairment on Nursing Home Residents

Abstract: Seventy nursing home residents with and 87 without cerebrovascular diseases (CVD) were examined by the modified Stockton Geriatric Rating Scale (modified SGRS) which measures four aspects of impairments; physical disability, socially irritating behavior, communication failure and apathy. They were divided into 3 subgroups according to walking ability; prolonged bed rest, walking with aids and walking by themselves in both groups. Physical disability of mental decline was significantly aggravated more than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Since grades 1 and 2 are rated as normal, their intellectual level was not clearly diminished. The present results along with prior studies (Nagatomo et al, 1992;Horiguchi et al, 1996) showed that the intellectual level of the elderly receiving home health services was higher compared with that of nursing home residents. Abnormal behaviors of the elderly such as agitation, combativeness, and wandering interfere with the provision of care in a nursing home, lower the morale of sta and detract from the QOL of the elderly (Rovner et al, 1986).…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…Since grades 1 and 2 are rated as normal, their intellectual level was not clearly diminished. The present results along with prior studies (Nagatomo et al, 1992;Horiguchi et al, 1996) showed that the intellectual level of the elderly receiving home health services was higher compared with that of nursing home residents. Abnormal behaviors of the elderly such as agitation, combativeness, and wandering interfere with the provision of care in a nursing home, lower the morale of sta and detract from the QOL of the elderly (Rovner et al, 1986).…”
Section: Discussionsupporting
confidence: 44%
“…We (Nagatomo et al, 1992) also have investigated the intellectual level of the elderly residing in a nursing home in Japan using the same assessment scales as the present study and estimated that about 40% showed mental decline. On the other hand, Horiguchi et al (1996) have investigated the elderly receiving home health services in a Prefecture in Japan and found that 80% of subjects were rated as having normal intellectual functioning, and only 5% of them were rated as having severe or extreme dementia.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations